OCORRÃŠNCIA NATURAL DE ð˜ˆð˜´ð˜±ð˜¦ð˜³ð˜¨ð˜ªð˜ð˜ð˜¶ð˜´ ð˜±ð˜¢ð˜³ð˜¢ð˜´ð˜ªð˜µð˜ªð˜¤ð˜¶ð˜´ EM POPULAÃ‡Ã•ES DE ð˜šð˜±ð˜°ð˜¥ð˜°ð˜±ð˜µð˜¦ð˜³ð˜¢ ð˜§ð˜³ð˜¶ð˜¨ð˜ªð˜±ð˜¦ð˜³ð˜¥ð˜¢ (ABBOT & SMITH, 1797) (LEPIDOPTERA, NOCTUIDAE) E SUA TRANSMISSÃƒO POR INSETOS PARASITOS - Patel, P. N.; Habib, M. E. M. (REVISTA DE AGRICULTURA, 2020)
OCORRÃŠNCIA NATURAL DE ð˜ˆð˜´ð˜±ð˜¦ð˜³ð˜¨ð˜ªð˜ð˜ð˜¶ð˜´ ð˜±ð˜¢ð˜³ð˜¢ð˜´ð˜ªð˜µð˜ªð˜¤ð˜¶ð˜´ EM POPULAÃ‡Ã•ES DE ð˜šð˜±ð˜°ð˜¥ð˜°ð˜±ð˜µð˜¦ð˜³ð˜¢ ð˜§ð˜³ð˜¶ð˜¨ð˜ªð˜±ð˜¦ð˜³ð˜¥ð˜¢ (ABBOT & SMITH, 1797) (LEPIDOPTERA, NOCTUIDAE) E SUA TRANSMISSÃƒO POR INSETOS PARASITOS